RANCANGAN PEMASANGAN SENSOR CAHAYA (PHOTOCELL) PADA LPJ DI KAWASAN PURA KHAYANGAN TIGA DESA TAMBAWU - Made Abdi Wiguna; Dewa Ayu Putu Adhiya Garini Putri; Wayan Sutama (Jurnal Pengabdian Masyarakat Teknik, 2022)
The advancement of technology in an electrical system is something that cannot be avoided as it develops, such as public facilities, and so on, it must follow a development in order to boost community work effectiveness and optimize existing devices in public areas. Lighting facilities at places of worship (temples) are still operational or manually operated, particularly in Tambawu Village. For energy and cost efficiency, this study seeks to install a light sensor (photocell) on street lighting in the Pura Khayangan Tiga, Tambawu Village area. The observation method, which is used to compute the overall use of sensors in lighting, the literature study approach, and the implementation of activities for linking lighting installations with a light sensor system were all employed in this study to collect some supporting data. Where the findings of this study illustrate the energy savings that occur when lighting is still operated manually versus when lighting is controlled by smart lighting or works automatically. Of course, the cost of paying for power tariffs on the lighting side demonstrates the energy savings. Where, the results of the efficiency that can be achieved have a difference of IDR 6,423.72 per month and IDR 77,084.64 per year, with operating costs in manual mode of IDR 52,455 and IDR 629,460,- per year and automatically amounting to IDR 46,031.28 and IDR 552,375.36 per year.